A combination of morphological and photosynthetic functional traits maintains the vertical distribution of bryophytes in a subtropical cloud forest. Issue 5 (25th May 2020) - Fan, Xiao-Yang; Liu, Wen-Yao; Song, Liang; Liu, Shuai; Shi, Xian-Meng; Yuan, Guo-Di
Abstract : Premise: The distribution and performance of bryophyte species vary with vertical gradients, as a result of changes in environmental factors, especially light. However, the morphological and physiological drivers of bryophyte distribution along forest vertical gradients are poorly understood. Methods: For 18 species of mosses and liverworts distributed among three vertical microhabitats (ground, tree trunk, and branch, variance in 28 morphological and photosynthetic functional traits was comparatively analyzed among the microhabitats and bryophyte life‐forms in a subtropical cloud forest in Ailao Mountain, Yunnan, southwestern China. Principal component analysis (PCA) was used to summarize trait differences among bryophyte species. Results: In contrast to trunk and ground dwellers, branch dwellers tended to reduce light interception (smaller leaf and cell sizes, lower chlorophyll content), protect against damage from intense irradiation (higher ratios of carotenoids to chlorophyll), raise light energy use (higher photosynthetic capacity), and cope with lower environmental moisture (pendant life‐forms, thicker cell walls). The PCA showed that ecological strategies of bryophytes in response to levels of irradiation were specialized in branch dwellers, although those of ground and trunk dwellers were less distinct. Conclusions: Environmental filtering shaped the combination of functional traits and the spatial distribution of bryophytes along the vertical gradients. Bryophyte species from the upper canopy of cloud forests show narrow variation in functional traits in high‐light intensity, whereas species in the lower vertical strata associated with low‐light intensity used contrasting, but more diverse ecological strategies.